FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI MASYARAKAT JABODETABEK TERHADAP PEMBELIAN PANEL SURYA ATAP - Rico Chandra; Antonius Haryo Tejo Sukmono; Eko Hery Wahyanto; Very Sebastian (Jurnal Manajemen, 2020)
This study aims to investigate the factors that might influence the buying decision of rooftop solar PV among consumers in Indonesia. This research was conducted by collecting 223 data as samples for analysis. Data collection was carried out using Google Forms and then analyzed with SPSS software. Based on the results of the analysis, there is a positive influence from factors such as environmental consciousness, attitude, green advertising, price and social belief towards the buying decision of rooftop solar PV. This study found that social beliefs, attitudes and prices are the significant factors that explained 37.4%, 20.3% and 17.9% of the buying decision. Meanwhile, eco-label is an insignificant factor in the buying decision.